Eschatology in the book of Malachi - Snyman, Fanie (Old Testament essays, 1988)
The main contribution of the book of Malachi to the subject of the eschatology oftheOId Testsment is found in Malachi 2:17-3:5 and 3:22- 24. In Malachi 3:1a one finds the introduction of a messenger of the Lord sent by him on a preparatory mission before Yahweh'. own coming - a feature only found in the book of Malachi and therefore a unique contribution to the eschatology of the Old Testament. While Malachi 3:1a echoes Isaiah 40:3 the messenger and the task assigned to him in Malachi 3:1a were still unspecified and vague enough to give rise to two different interpretations, the one found in Malachi 3:1b-4 and theotber in Malachi 3:23-24. Although some identity is presumed between the figure in Malachi 3:1a and Elijah in 3:23- 24 it is argued that no identification can be established between the figure in 3:1h-'4 and Elijah in 3:23-24. The paper also investigates other (possible) eschatological pericopes (MI3:13-21; 3:6-12; 1:2-5; 1:11) before some conclusions are made.